Analisis Makna Sebutan “Allah Anak” Dan “Anak Allah” Perspektif Biblika (Markus 1:1) : Penelitian - Ruben Nesimnasi; Prasetyo, Edhi; Siregar, Humala Andi Aposan; Wahyu, Tan Markus Setiadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article examines the theological significance of the designations “Son of God” and “God the Son” in the biblical perspective of Mark 1:1. The study argues that while “Son of God” emphasizes the relational and functional aspects of Christ’s identity within the Trinity, “God the Son” highlights His eternal divine nature as affirmed in the Nicene Creed. Employing exegetical, hermeneutical, and theological approaches through qualitative library research, this study seeks to clarify the Christological implications of both terms. The findings indicate that these designations are not contradictory but complementary, shaping a deeper understanding of Christ’s divinity and humanity for both the early church and contemporary Christian theology.